Low-pressure membrane technology for potable water filtration: true costs - Judd, Simon J.; Carra, Irene (Elsevier, 2021)
The overall cost, expressed as the present value (PV), of the construction and operation of low-pressure membrane filtration of inland water for potable water supply has been determined for membrane installations across the UK. The analysis was based on 15 full-scale installations installed with hollow fibre and capillary tube polymeric membranes, for which cost and related data were available. The analysis encompassed labour, in addition to energy, chemicals and critical component replacement. PV data were presented as functions of flow capacity (i.e. as cost curves), delineated as capital (CAPEX), operating (OPEX) and total PV normalised against flow rate (PV’) the CAPEX excluding the site-specific civil engineering costs. Captured CAPEX data revealed these to be lower than those previously reported, and with a reduced economy of scale. The OPEX PV exceeded the CAPEX by a factor of 3-6 based on a 20-year life cycle, the difference increasing with decreasing flow capacities. Costs associated with unplanned (or “reactive”) maintenance, partly associated with the repair of breached membranes and/or permeability recovery following membrane clogging, were found to make up around half the labour costs. Labour costs as a proportion of the flow increased with decreasing flow, exceeding the CAPEX at flows below 30,000 m3/d. Outcomes indicate labour costs associated with process upsets to contribute significantly to the overall cost of the installation over its life cycle, particularly at flows below ~30,000 m3/d. A clear trade-off exists between supplementary capital investment to allay process upsets and the operational costs associated with such events.
Keywords: Low-pressure membranes; cost; present value; labour; process upset